Plasma neurofilament light, glial fibrillary acid protein, and phosphorylated tau 181 as biomarkers for neuropsychiatric symptoms and related clinical disease progression - Rabl, Miriam; Zullo, Leonardo; Lewczuk, Piotr; Kornhuber, Johannes; Karikari, Thomas K.; Blennow, Kaj; Zetterberg, Henrik; Bavato, Francesco; Quednow, Boris B.; Seifritz, Erich; von Gunten, Armin; Clark, Christopher; et al. (Alzheimer's Research and Therapy, 2024)
Background: Neuropsychiatric symptoms (NPS) are common in older people, may occur early in the development of dementia disorders, and have been associated with faster cognitive decline. Here, our objectives were to investigate whether plasma levels of neurofilament light chain (NfL), glial fibrillary acid protein (GFAP), and tau phosphorylated at threonine 181 (pTau181) are associated with current NPS and predict future NPS in non-demented older people. Furthermore, we tested whether the presence of NPS combined with plasma biomarkers are useful to predict Alzheimer’s disease (AD) pathology and cognitive decline. Methods: One hundred and fifty-one participants with normal cognition (n = 76) or mild cognitive impairment (n = 75) were examined in a longitudinal brain aging study at the Memory Centers, University Hospital of Lausanne, Switzerland. Plasma levels of NfL, GFAP, and pTau181 along with CSF biomarkers of AD pathology were measured at baseline. NPS were assessed through the Neuropsychiatric Inventory Questionnaire (NPI-Q), along with the cognitive and functional performance at baseline and follow-up (mean: 20 months). Different regression and ROC analyses were used to address the associations of interest. Results: None of the three plasma biomarker was associated with NPS at baseline. Higher GFAP levels were associated with the presence of NPS at follow-up (OR = 2.8, p =.002) and both, higher NfL and higher GFAP with an increase in the NPI-Q severity score over time (β = 0.25, p =.034 and β = 0.30, p =.013, respectively). Adding NPS and the plasma biomarkers to a reference model improved the prediction of future NPS (AUC 0.72 to 0.88, p =.002) and AD pathology (AUC 0.78 to 0.87, p =.010), but not of cognitive decline (AUC 0.79 to 0.85, p =.081). Conclusion: Plasma NfL and GFAP are both associated with future NPS and NPS severity change. Considering the presence of NPS along with blood-based AD-biomarkers may improve the prediction of clinical progression of NPS over time and inform clinical decision-making in non-demented older people.
CRIS-Team Scopus Importer:2024-08-02
Keywords: Alzheimer’s disease; Blood-based biomarkers; Cognition; GFAP; Glial fibrillary acid protein; Neurofilament light chain; Neuropsychiatric symptoms; NfL; Phosphorylated tau 181; pTau181